2021
DOI: 10.1038/s41370-021-00366-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 test positivity rate in Reno, Nevada: association with PM2.5 during the 2020 wildfire smoke events in the western United States

Abstract: Background Air pollution has been linked to increased susceptibility to SARS-CoV-2. Thus, it has been suggested that wildfire smoke events may exacerbate the COVID-19 pandemic. Objectives Our goal was to examine whether wildfire smoke from the 2020 wildfires in the western United States was associated with an increased rate of SARS-CoV-2 infections in Reno, Nevada. Methods We conducted a time-series analysis using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…During 2020, air quality reached unhealthy and hazardous levels in the western United States due to wildfires, which coincided with the spread of COVID-19. Epidemiological evidence has shown that worsened air quality from PM is associated with increased COVID-19 case rate and case fatality rate around the world ( 31 37 , 39 , 40 ). Toxicological studies have indicated that PM exposure affects the host defense response of the airways on viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During 2020, air quality reached unhealthy and hazardous levels in the western United States due to wildfires, which coincided with the spread of COVID-19. Epidemiological evidence has shown that worsened air quality from PM is associated with increased COVID-19 case rate and case fatality rate around the world ( 31 37 , 39 , 40 ). Toxicological studies have indicated that PM exposure affects the host defense response of the airways on viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies from around the world have found correlations between ambient air pollution levels and COVID-19 case number or case fatality rate ( 31 35 ). Recently, two studies found positive associations between ambient woodsmoke particles (WSPs) and COVID-19 cases and deaths in the western United States ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary transmission routes are also plausible. For example, air quality can be reduced due to higher levels of pollutants from wildfires and other activities, which have shown to lead to strong impacts upon contracting COVID-19 ( Liu et al, 2020a ; Meo et al, 2020 ; Middleton, 2020 ; Curtis, 2021 ; Dragone et al, 2021 ; Kiser et al, 2021 ; Leifer et al, 2021 ; Setti et al, 2020 b; Zhou et al, 2021 a). Furthermore, natural ventilation for optimal indoor air quality is not sufficient to control the potential spread of SARS-CoV-2 ( Li et al, 2004 ; Meiss et al, 2021a ; WHO, 2021a).…”
Section: Impact Of Ambient Environments On Sars-cov-2mentioning
confidence: 99%
“…To examine this hypothesis, we use data from a monitoring site in Sparks, NV, near Reno, a region that has been heavily influenced by smoke in the past several years due to the large number and extent of California wildfires. Data from this region were recently used to examine the role of high PM2.5 exposure from smoke on COVID-19 incidence (Kiser et al 2021). From the Sparks, NV observations, we develop a quantitative model using a Monte Carlo simulation that provides a range of probabilistic results that can be compared to observations.…”
Section: Introductionmentioning
confidence: 99%